Early morphology in Berbice Dutch and source language access in creolisation. (October 2015) - Kouwenberg, Silvia
<x content-type="archive" xml:space="preserve">Abstract</x> After sketching the historical background to the emergence of Berbice Dutch (BD) in the Dutch-owned Berbice colony, I consider the composition of the BD lexicon, showing that this creole language received input from three linguistic sources, one European (Dutch, mainly Southwestern varieties), one African (one or several Eastern Ijo lects), and one native American (Arawak). While the latter is essentially a source of culturally specific borrowings, Dutch and Eastern Ijo are both well represented in common semantic domains of the lexicon. The remainder of the paper focuses on BD bound morphemes in the nominal and verbal domains, all of which derive from forms in the substrate; the striking absence of Dutch-origin morphology is considered, as is the reanalysis of substrate-origin morphology and the general lack of comparability of the distinctions made in the BD and Eastern Ijo nominal and verbal domains. I argue that despite the presence of Dutch and Eastern Ijo speakers – and hence of unsimplified Dutch and Eastern Ijo in the context in which BD emerged – creolisation proceeded without full access to the source languages.